The defense lawyer [compact disc, unabridged] - Patterson, James, 1947-; Wallace, Benjamin, 1968- (Hachette Audio, 2021)
Everyone deserves the best defense. Known for his sharp mind, sharp suits, and bold courtroom strategies, Bronx-native Bernard Slotnick is known as the best criminal lawyer in the US.